Validation of plasma D-dimer in Chinese patients with acute non-ST segment elevation myocardial infarction - Fan, Xin; Min, Tingting; Su, Shaohui; Xiong, Bin; Wan, Huaibin (Frontiers in Cardiovascular Medicine, 2022)
Objective To analyze the predictive values of D-dimer in Chinese patients with non-ST-segment elevation myocardial infarction (NSTEMI). Methods We retrospectively retrieved consecutive patients hospitalized due to acute NSTEMI from January 2015 to December 2018 from the Electronic Medical Record (EMR) library. Clinical and follow-up data were collected. The primary endpoint was major adverse composite cardiovascular events (MACEs), such as all-cause death, non-fatal myocardial infarction, and non-fatal stroke. The secondary endpoints included all-cause death, non-fatal myocardial infarction, non-fatal stroke, heart failure, and severe arrhythmias. The Cox regression model was used to evaluate the association between risk factors and clinical outcomes in Chinese patients with NSTEMI. Results A total of 673 patients were included; the median age was 64.0 (53.0–75.0) years old and 76.2% were men. Patients with higher D-dimer levels were more often women, older, had a higher Charlson Comorbidity Index, and had a higher incidence of MACEs (59.9 vs. control 9.0%; p < 0.001) and all-cause death (49.1 vs. control 2.2%; p < 0.001). The multivariate Cox analysis suggested that the D-dimer level was an independent predictor of MACEs (hazard ratio [HR]: 1.069, 95% CI: 1.010–1.132, p = 0.021). The receiver operating characteristic (ROC) analysis suggested that D-dimer levels were better than the Charlson Comorbidity Index in all-cause death. Conclusion In Chinese patients with acute NSTEMI, higher D-dimer levels on admission suggest a poor long-term prognosis.